Poetika književnog opusa Lukrecije Bogašinović - Plejić, Lahorka (1997)
The literary opus by Lukrecija Bogašinovic (three Biblical cantos and a Christmas pastoral) belongs to the corpus of texts which stand out for their conservatism, strong religious feelings and their orientation to the uneducated (female) readership. All four texts are firmly rooted in the literary tradition of Dubrovnik Baroque, Vetranovic being one of its most prominent representatives. It is in this tradition that the poetess Bogašinovic found her themes, ideological components, style and verse patterns. Thus in order to describe her potry it is important to consider the tradition her texts reflect on different levels and in different ways.
Projekt MZOS
HRV